2020
DOI: 10.1111/apt.15681
|View full text |Cite
|
Sign up to set email alerts
|

Bowel damage and disability in Crohn's disease: a prospective study in a tertiary referral centre of the Lémann Index and Inflammatory Bowel Disease Disability Index

Abstract: Background: The notion of Crohn's disease (CD) as a chronic, progressive and disabling condition has led to the development of new indexes: the Lémann Index measuring cumulative bowel damage and the Inflammatory Bowel Disease (IBD) Disability Index, assessing functional disability.Aims: To measure the Lémann Index and the IBD Disability Index in a large prospective cohort of CD patients and to assess the correlation between these two indexes. Methods:We performed a prospective study in a tertiary referral cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 31 publications
1
18
0
Order By: Relevance
“…Drs Creemers, Bloem and Bodegraven also underlined that our result showing that there was no correlation between the Lémann index and the IBD Disability Index, is logical 4 . Indeed, the subjective aspect of the IBD Disability Index score is obvious because it measures disability which is correlated in part to quality of life 5,6 .…”
mentioning
confidence: 55%
“…Drs Creemers, Bloem and Bodegraven also underlined that our result showing that there was no correlation between the Lémann index and the IBD Disability Index, is logical 4 . Indeed, the subjective aspect of the IBD Disability Index score is obvious because it measures disability which is correlated in part to quality of life 5,6 .…”
mentioning
confidence: 55%
“…It has been shown to accurately parallel disease progression in CD [ 22 , 112 ], but evidence about its utility with the different treatments is still limited. Biologics, and specifically anti-TNFs, have been shown to be effective in stopping, and even reducing, cumulative damage as measured by this index [ 113 , 114 ]. However, more data are still needed about its application with the remaining drugs currently used in clinical practice.…”
Section: Early CDmentioning
confidence: 99%
“…The study by Lauriot dit Prevost et al 1 showed that there was no (or limited) correlation between the Lémann index and the IBD‐DI. Hence intestinal damage and patient‐reported outcome (experience) assess different domains of a Crohn’s disease patient.…”
mentioning
confidence: 98%
“…In a recent prospective study assessing the Lémann Index and the Inflammatory Bowel Disease‐Disability Index (IBD‐DI) in 130 outpatients with Crohn's disease, factors associated with extensive bowel damage and severe disability were identified 1 . Furthermore, the correlation between the Lémann Index, designed to objectify accumulative intestinal structural damage, and the IBD‐DI, being a patient‐reported outcome measure (PROM) of disease‐associated disability, was calculated.…”
mentioning
confidence: 99%
See 1 more Smart Citation